PROVIDENCE, STATUTES OF THE STATE OF RHODE ISLAND RELATING TO THE CITY AND ORDINANCES OF THE CITY, ch. 5, § 105 (Riverside Press 1875). - (:unkn) unknown (General Publisher, 1874)
He may also arrest without a warrant any person reasonably suspected of having committed a felony, or seen committing a breach of the peace, or being unduly armed with a dangerous weapon, and also night-walkers.
--
Keywords: POSSESSION - DANGEROUS PERSONS